Biased Ghrelin Receptor Signaling and the Dopaminergic System as Potential Targets for Metabolic and Psychological Symptoms of Anorexia Nervosa - Khelifa, Mariam S.; Skov, Louise J.; Holst, Birgitte (Frontiers in Endocrinology, 2021)
Anorexia Nervosa (AN) is a complex disease that impairs the metabolic, mental and physiological health of affected people in a severe and sometimes lethal way. Many of the common symptoms in AN patients, such as reduced food intake, anxiety, impaired gut motility or overexercising are connected to both the orexigenic gut hormone ghrelin and the dopaminergic system. Targeting the ghrelin receptor (GhrR) to treat AN seems a promising possibility in current research. However, GhrR signaling is highly complex. First, the GhrR can activate four known intracellular pathways Gαq, Gαi/o, Gα12/13 and the recruitment of β-arrestin. Biased signaling provides the possibility to activate or inhibit only one or a subset of the intracellular pathways of a pleotropic receptor. This allows specific targeting of physiological functions without adverse effects. Currently little is known on how biased signaling could specifically modulate GhrR effects. Second, GhrR signaling has been shown to be interconnected with the dopaminergic system, particularly in the context of AN symptoms. This review highlights that a biased agonist for the GhrR may be a promising target for the treatment of AN, however extensive and systematic translational studies are still needed.